The development of effective oral production through the use of technological resources on students from seventh grade at Santo Domingo de Guzman, school year 2016-2017 - Calderón Valencia, Manuela Andrea (2017)
The present Project was conducted with students of seventh grade at Santo Domingo De Guzman. The project was designed for students to improve their learning speaking skills because it is one the most challenging skills that students face when learning the English language. The general objective of this project was to analyse the impact that educational portals have in the learning process. Schools face the obstacle on the daily basis with all their English learning students, but involving technology there should show progress. It has become a predictable problem among teachers, students, parents and the education system when English is mentioned, especially if technology in such language is also involved…..